Towards an environment for data mining based analysis processes in bioinformatics and personalized medicine - Wegener, D; Rossi, S; Buffa, F; Delorenzi, M; Rüping, S (2011)
Bioinformatics and data mining procedures are collaborating to implement and evaluate tools and procedures for prediction of disease recurrence and progression, response to treatment, as well as new insights into various oncogenic pathways [1], [2], [3], [4] by taking into account the user needs and their heterogeneity. Based on these advances, medicine is undergoing a revolution that is even transforming the nature of health care from reactive to proactive [5]. The p-medicine (www.p-medicine.eu) consortium is creating a biomedical platform to facilitate the translation from current practice to a predictive, personalized, preventive, participatory and psycho-cognitive medicine by integrating VPH models, clinical practice, imaging and omics data. In this paper, we present the challenges for data mining based analysis in bio-and medical informatics and our approach towards a data mining environment addressing these requirements in the p-medicine platform. © 2011 IEEE.